A GENRE-BASED APPROACH TO TEACHING WRITING DESCRIPTIVE TEXT : A Case Study in Seventh Grade Students in a Junior High School in Lembang - Irianti, Ira (2015)
This study investigates how the implementation of Genre-Based Approach can help students to write a Descriptive text in one public junior high school in Lembang, West Java. This study also investigates students' responses towards the implementation of genre-based approach to teaching writing Descriptive text. This study utilizes a case study research design. The data were obtained from classroom observation, analysis of students' texts, and interview with students. Data from classroom observation were analyzed using a thematic analysis to investigate the implementation of genre-based approach. The students' writing products were analyzed in terms of the description of schematic structures, including the analysis of general statement and description, and linguistic features of Descriptive text as proposed by Derewianka (2004), Emilia (2010, 2012), Gerot and Wignell (1994), Knapp & Watkins (2005). The analysis is based on of Systemic Functional Linguistics including Transitivity system and Conjunction as proposed by Gerot and Wignell (1994), Halliday (1994), and Eggins (2004). Finally, the interview data were analyzed in steps including transcribing, categorizing, and interpreting the data relating them to the theory. Data from the study reveal that the implementation of genre-based approach to teaching descriptive text can help develop students' writing ability. This can be seen from the students' decriptive texts which improved in terms of schematic structure and linguistic features with the teacher's corrective feedback in all stages of teaching. Moreover, the interview data reveal that generally the students gave positive responses to the teaching program, that the program can help them express ideas on their texts. Based on the findings, it is recommended that Genre-Based Approach should be used in teaching different genres and different levels of schooling. Keywords: Writing, Genre Based-Approach, Systemic Functional Linguistics, Descriptive Text Penelitian ini bertujuan untuk menguji bagaimana implementasi GBA yang dapat membantu siswa dalam menulis sebuah deskriptif teks di sebuah SMP negeri di Lembang. Penelitian ini juga bertujuan untuk menguji respon siswa terhadap implementasi GBA dalam pengajaran menulis deskriptif teks. Penelitian ini menggunakan desain penelitian studi kasus. Data penelitian yang diperoleh dari observasi kelas, analisis hasil tulisan siswa, dan wawancara dengan siswa. Setelah diperoleh hasil dari tulisan-tulisan siswa, sembilan diagnosis teks dan sembilan tulisan akhir dari sembilan siswa yang mewakili siswa berprestasi rendah, menengah dan tinggi dianalisis dalam hal struktur teks termasuk analisis dari pernyataan umum dan deskripsi dan fitur linguistik dari deskriptif teks yang telah dikemukakan oleh Derewianka (2004), Emilia (2010), Gerot dan Wignell (1994), Knapp & Watkins (2005). Analisis ini merupakan dasar dari SFL termasuk sistem transitif dan kata penghubung yang telah dikemukakan oleh Gerot dan Wignell (1994), Halliday (1994), dan Eggins (2004). Akhirnya, data wawancara dianalisis secara bertahap, menyalin, mengkategorikan dan menafsirkan data mengaikatkannya dengan teori. Temuan menunjukkan bahwa implementasi GBA dalam pengajaran deskriptif teks membuat kontribusi yang baik untuk pengembangan menulis siswa. Dan lagi, deskripsi teks siswa mengalami peningkatan dalam hal strukrur teks dan fitur linguistik dengan umpan balik korektif guru di dalam setiap tahap pengajaran. Selain itu, dari data wawancara menunjukan keseluruhan siswa memberikan respon positif terhadap program pengajaran. Karena siswa mendapat kosakata yang baru dan dapat menghasilkan dan menyusun ide-ide dalam deskripsi teks masing-masing. Berdasarkan hasil ini, bahwa direkomendasikan program pengajaran GBA ini disosialisakan dalam konteks dan tingkat pendidikan yang lain. Kata kunci : Menulis, Genre-Based Approach (GBA), Systemic Functional Linguistics (SFL), teks Descritive